Peran Ukuran Perusahaan sebagai Variabel Moderasi dari Profitabilitas dan Leverage Terhadap Pengungkapan Sustainability Report - Purnomo, Radian Rachmadi; Ulupui, I Gusti Ketut Agung; Yusuf, Muhammad (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study aims to analyse the effect of profitability and leverage on sustainability report disclosure with company size as a moderating variable. Infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2020-2023 are used as research objects with secondary data in the form of annual reports and sustainability reports. There are 20 companies selected based on purposive sampling technique with a total of 74 unbalanced observation data. This research was processed using panel data regression and moderation regression in the E-views 13 application with the selected model, namely the random effect model. The results of this study indicate that profitability has no effect on sustainability report disclosure. While leverage has a positive effect on sustainability report disclosure. Firm size does not moderate either profitability or leverage on sustainability report disclosure.